Implementation of Curfew Policy for Students in Bandung City from the Perspective of Public Policy and Government Ecology - Rahmatullah, Aji; Prasetyo, Shakila Adzira Putri; Januariska, Nazwa Nafisha (Universitas Ibn Khaldun Bogor, 2025)
This study explores the implementation of the curfew policy for students in Bandung City as a response to rising juvenile delinquency. Using a qualitative approach, the study employs interviews and document analysis, grounded in George C. Edwards III's policy implementation model and the ecological approach to governance. The findings reveal that from a public policy perspective, the implementation encounters challenges in communication, due to the absence of technical guidelines, limited resources, poor bureaucratic coordination, and incomplete disposition among implementers and communities. From the perspective of government ecology, the policy is shaped by external factors such as geographical conditions, youth human resource quality, and socio-cultural values, while internal factors such as leadership vision, bureaucratic culture, institutional synergy, and parental and teacher involvement significantly affect policy effectiveness. The policy also risks negative labeling if implemented in a repressive manner.